2016
DOI: 10.1080/1350293x.2016.1164398
|View full text |Cite
|
Sign up to set email alerts
|

Directly observed physical activity and fundamental motor skills in four-year-old children in day care

Abstract: Physical activity (PA), its location, social interactions and fundamental motor skills were investigated in four-year-old Finnish children in day care. Six skills in the stability, locomotor and manipulative domains were assessed in 53 children (24 boys, 29 girls, normal anthropometry) with the APM-Inventory manual for assessing children's perceptual and fundamental motor skills (Numminen, 1995) and Total Motor Scores (TMS; 0-6 points) calculated. PA intensity, location, group composition and activity type − s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
0
21
0
1
Order By: Relevance
“…32 Based on the results of our study and speculating more, it is possible that in Finnish day care, more attention is paid to the type of physical activities children engage in and the context, for example playing outside, rather than the amount of PA. For example, in a recent Finnish study, children who were more physically active outdoors scored higher in six measured motor skills, but the PA was not significantly associated with total motor skills. 33 Indeed, in the study region, outdoor day care is becoming increasingly popular 34 and that might have an influence on motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…32 Based on the results of our study and speculating more, it is possible that in Finnish day care, more attention is paid to the type of physical activities children engage in and the context, for example playing outside, rather than the amount of PA. For example, in a recent Finnish study, children who were more physically active outdoors scored higher in six measured motor skills, but the PA was not significantly associated with total motor skills. 33 Indeed, in the study region, outdoor day care is becoming increasingly popular 34 and that might have an influence on motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…Next, in a large study with 2-year-old children who were typically developing, no correlation was found between fine, gross, or total movement scores and objectively measured physical activity (Johansson et al, 2015) Similarly, in a group of preschool-aged children (mean age = 4 years), total motor proficiency (i.e. stability, locomotion, and manipulative skills) was not significantly associated with directly observed physical activity (Livonen et al, 2016). Therefore, while this relationship remains somewhat inconclusive in preschool-aged children, there appears to be more consensus as children age, suggesting that the association between motor skills and physical activity albeit weak early on actually strengthens throughout development (Stodden et al, 2008).…”
mentioning
confidence: 92%
“…Such other difficulties as an excessive ratio of pupils to teachers, a lack of resources, few physical spaces designated for this practice, time shortage, and inflexible timetables negatively impact teacher motivation, and contribute to an increasingly sedentary lifestyle that can reduce children's psychomotor development (Arufe & Pons, 2016;Iivonen et al, 2016;Storli & Hagen, 2010).…”
Section: Introductionmentioning
confidence: 99%